Leveraging Social Media for Learning: Exploring Effectiveness and Best Practices (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Social media has emerged as a ubiquitous platform with vast potential for enhancing learning experiences in educational settings. This article investigates the effectiveness of social media for learning and explores best practices for its integration into pedagogical practices. Drawing upon a review of existing literature and empirical studies, this article examines the benefits, challenges, and considerations associated with leveraging social media platforms in educational contexts. Key findings highlight the role of social media in promoting student engagement, facilitating collaborative learning, and fostering communication and interaction among students and educators. By providing insights into the effectiveness of social media for learning and offering practical recommendations, this article aims to inform educators, administrators, and policymakers seeking to harness the potential of social media in enhancing educational out comes.